Parliamentary government in Australia - Ward, Alan J. 1937- (Anthem Press, 2014)
This volume combines constitutional history and political science to compare all nine of Australia's political systems, federal, state and territory, from colonial times to the present
First published in Australia by Australian Scholarly Publishing 2013
Keywords: Australien -- Government; Geschichte; Repräsentative Demokratie; Parlamentarismus; Australia / Parliament; Representative government and representation / Australia; Cabinet system / Australia; Legislative power / Australia; Executive power / Australia; Australia / Politics and government; Cabinet system; Executive power; Legislative power; Politics and government; Representative government and representation; Australia